(untitled) (TAJ: Journal of Teachers Association, 2018)
We evaluate 600 patient with clinically unhealthy cervix with colposcope and cervical punch biopsy was taken from each patient for further evaluation. Patient & Methods: This is a cross sectional descriptive study carried out in colposcopy center of RMCH from January to December 2014. We reviewed all patient aged 18 to 60 years having clinically unhealthy cervix, who attended colposcopy center during study period. Results: Among 600 patient with unhealthy cervix 150 patient present with cervical erosion that is 25% patient present with erosion, 96 patient presented with congestion that is 16% with congestion, 30 patient presented with polyp that is 5%, 84 patient presented with excessive P/V discharge that is 14%, 73 patient with hypertrophied cervix that is 12%, patient with hypertrophied cervix and among all patient 96 patient was colposcopically diagnosed as CIN (72 with CIN-I, 12 with CIN-II, 12 with CIN-III, that is 16% patient has CIN, in 97 patient findings was unsatisfactory. Histopathologically 72 has CIN, among these 48 has CIN-I, 18 with CIN-II, & 6 with CIN-III that is 12% patient was histopathologically diagnosed as CIN. And 6 patient diagnosed as invasive carcinoma. Conclusion: So from this study we get a good information regarding prevalence of CIN among unhealthy looking cervix. And there is good correlation between colposcopy & histopathology findings. TAJ 2013; 26: 3-7